Protocol to assess the impact of tobacco-induced volatile organic compounds on cardiovascular risk in a cross- sectional cohort: Cardiovascular Injury due to Tobacco Use study. Issue 3 (30th March 2018) - Keith, Rachel J; Fetterman, Jessica L; Riggs, Daniel W; O'Toole, Timothy; Nystoriak, Jessica L; Holbrook, Monika; Lorkiewicz, Pawel; Bhatnagar, Aruni; DeFilippis, Andrew P; Hamburg, Naomi M
Abstract : Introduction: Tobacco use leads to increased mortality, the majority of which is attributed to cardiovascular disease. Despite this knowledge, the early cardiovascular impact of tobacco product use is not well understood. Tobacco use increases exposure to harmful and potentially harmful constituents including volatile organic compounds (VOCs) such as acrolein and crotonaldehyde, which may contribute to cardiovascular risk. The link between exposure patterns, risk profiles and demographic distribution of tobacco product users, particularly users of new and emerging products, are not well known. Therefore, we designed the Cardiovascular Injury due to Tobacco Use (CITU) study to assess population characteristics, demographic features, exposure patterns and cardiovascular risk in relation to tobacco. Methods and analysis: We present the design and methodology of the CITU study, a cross-sectional observational tobacco study conducted in Boston, Massachusetts and Louisville, Kentucky starting in 2014. Healthy participants 21–45 years of age who use tobacco products, including electronic nicotine devices, or who never used tobacco are being recruited. The study aims to recruit an evenly split cohort of African-Americans and Caucasians, that is, sex balanced for evaluation of self-reported tobacco exposure, VOC exposure and tobacco-induced injury profiling. Detailed information about participant's demographics, health status and lifestyle is also collected. Ethics and dissemination: The study protocol was approved institutional review boards at both participating universities. All study protocols will protect participant confidentiality. Results from the study will be disseminated via peer-reviewed journals and presented at scientific conferences.